Liquid-phase synthesized mesoporous electrochemical supercapacitors of nickel hydroxide - Chang, Jinho; Park, Mira; Ham, Dukho; Ogale, S. B.; Mane, Rajaram S.; Han, Sung-Hwan (Electrochimica Acta, 2008)
Electrochemical supercapacitive (ES) properties of liquid-phase synthesized mesoporous (pore size distribution centered similar to 12 nm) and of 120 m(2)/g surface area nickel hydroxide film electrodes onto tin-doped indium oxide substrate are discussed. The amounts of inner and outer charges are calculated to investigate the contribution of mesoporous structure on charge storage where relatively higher contribution of inner charge infers good ion diffusion into matrix of nickel hydroxide. Effect of different electrolytes, electrolyte concentrations, deposit mass and scan rates on the current-voltage profile in terms of the shape and enclosed area is investigated. Specific capacitance of similar to 85 F/g at a constant current density of 0.03 A/g is obtained from the discharge curve. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: electrochemical supercapacitors; mesoporous structure; nickel hydroxide